PEMIKIRAN POLITIK MOHAMMAD HATTA TENTANG DEMOKRASI - Pangeran Nagari Hutabarat; Priyatno Harsasto; Susilo Utomo (Journal of Politic and Government Studies, 2015)
AbstractMohammad Hatta or Mr. Hatta is a pioneer figure of human rights movement in Indonesia. There are reasons to confirm Mr. Hatta as the pioneer figure of human rights movement in Indonesia. First, Mr. Hatta is judged as the main person to create the foundation of modern democratic constitutional nation, both in the level of values and the practice of it’s development. Second, Mr. Hatta is regarded as the pioneer of democracy. It was seen on 3rd November 1945, when the government issued a declaration signed by Mr. Hatta as the Vice President which proclaimed the creation of political parties. Therefore, that occasion underlining the nullification of the single party nation while most of political elite regarded the single party nation with Partai Nasional Indonesia was the best idea.The purpose of this research is to indentify the solution from the weakness of individualism concept in democracy so that it can be applied in Indonesia, also to identify the effectivity of democratic system, and to describe a democracy that should be applied in Indonesia. The method used in this research is literature review. There are four indicators in Mr. Hatta’s idea. i.e: Individualism vs. Collectivism, Democracy, People’s Sovereignty, and Economic System.Mohammad Hatta rejects democracy that focused on individualism, because in the later people’s development, the capitalists were the ones who can reap most benefit from it. Economic democracy contains the idea of social-economy decison making pattern by the hand of majority public.This idea is contrary to the monopolistic economical structure which progressively limit the access of majority of working-class people against the chances and economic resources. The rationality is based on the idea that full political rights can’t be obtained without full economic rights. To ensure the democratic economy governance and to ensure appropriate distribution of economic resources, political control and law enforcement, therefore it should be returned to people’s majority.In macro point of view, some of the postulations from Mr. Hatta’s exemplary manner and idea still very relevant today. People’s sovereignty and collectivism can only be done if accompanied by democratic economy. According to Mr. Hatta, the main pillar in creating democratic economy is Cooperative Business.Keywords: Mohammad Hatta, Democracy, People’s Sovereignty, Human Rights